Disclosure of the Author's Conflict of Interest: Why? - Anastasiya S. Ostrovskaya ("Paediatrician" Publishers LLC, 2016)
The article describes not only the concept of conflict of interest, but also the validity of its disclosure in the texts of scientific medical articles. The issue of non-disclosure of conflict of interest is analyzed by the authors of the Russian journals. The examples that demonstrate the need to declare the conflict are given. A form for the disclosure of conflict of interest when submitting a manuscript for consideration is proposed.